1934
DOI: 10.1002/zaac.19342180406
|View full text |Cite
|
Sign up to set email alerts
|

Über die thermische Analyse des Systems Schwefelsäure/Wasser und die Tieftemperaturdichten kristallisierter Schwefelsäurehydrate

Abstract: Die Raumchemie der Hydrate fordert die Kenntnis der Nullpunktsvolumina der Verbindungen von Schwefelsaure mit Wasser. Die Vorfrage dazu, welche Schwefelsaurehydrate existieren, war noch nicht vollig beantwortet. Allerdings liegen seit PFAUNDLER (1875) zahlreiche Beobachtungen uber das Schmelzen und Erstarren von Schwefelsaurehydraten vor, und MEYERHOFFER hat sie zu dem bekannten Schaubilde zusammengefafit, das sich in den Tabellen von LANDOLT-BORNSTEIN findet2). Indessen fehlen in dem Bilde die eutektischen Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

1960
1960
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 3 publications
0
20
0
Order By: Relevance
“…If we take this to be an indication that these samples are very near the hydrate stoichiometric composition, then we note that 35. 3 20 However, they did not use a 1:8 H 2 SO 4 /H 2 O solution to make singlecrystal SAO. Instead they used a 37.7 wt % solution to produce the crystals used in their experiments.…”
Section: Resultsmentioning
confidence: 97%
“…If we take this to be an indication that these samples are very near the hydrate stoichiometric composition, then we note that 35. 3 20 However, they did not use a 1:8 H 2 SO 4 /H 2 O solution to make singlecrystal SAO. Instead they used a 37.7 wt % solution to produce the crystals used in their experiments.…”
Section: Resultsmentioning
confidence: 97%
“…Sulfuric acid tetrahydrate (SAT) particles are the thermodynamically stable form of H 2 SO 4 /H 2 O mixtures over a wide range of stratospheric conditions (Middlebrook et al., 1993; Koop & Carslaw, 1996). However, laboratory experiments have reported that solutions of H 2 SO 4 at 195 K require tempering for days to achieve crystallization as a hydrate (Hülsmann & Biltz, 1934; Luo et al., 1994; and references therein). Direct observational evidence to date that SAT particles exist in the atmosphere is lacking or questionable.…”
Section: Formation Pathways and Particle Characteristicsmentioning
confidence: 99%
“… a 1, CRC Handbook; 2, Hulsmann; 3, Luzzati; 4, Luzzati . See text for a description of how the other molar volumes and densities were obtained. …”
mentioning
confidence: 99%